Clinical utility of ultrasound by general practitioners: a systematic review - Claudio Schneider; Andreas Stalder; Nadia Ennaciri; Aude Eckert; Elena Hofmann; Martin Müller; Carole E. Aubert (BMC Primary Care, 2026)
Abstract Background The clinical use of ultrasound by general practitioners has expanded rapidly, but uncertainty persists in clinical practice regarding which indications can improve diagnostic process and which rather represent low-value care. Methods We conducted a systematic review of clinical guidelines published between 2014 and 2024 addressing ultrasound indications relevant to general practitioners. Searches were performed in MEDLINE, Embase, CINAHL, Cochrane, and major guideline repositories. Two reviewers independently screened records, extracted recommendations, and assessed quality using the AGREE II instrument. Recommendations were categorized by clinical condition, level of evidence, and strength of recommendation. Results Of 4015 records, 108 guidelines were included. A total of 293 recommendations (from 95 guidelines) supported the use of ultrasound (Strength of Recommendation A/B), while 66 recommendations (from 17 guidelines) discouraged its use (Strength of Recommendation D). Most appropriate indications involved cardiovascular, gastrointestinal, musculoskeletal, and respiratory conditions, while the majority of low-value indications were found in the endocrinological, urological, and vascular conditions. Overall, methodological quality ranged from moderate to high: 70 (64.8%) guidelines were rated as high quality, while 38 (35.2%) showed moderate quality. Conclusions Ultrasound provides important clinical value for general practitioners, with many high-quality guidelines supporting its use for evidence-based indications. However, a substantial number of recommendations also highlight scenarios where ultrasound offers little benefit or is inappropriate, underscoring the need for more selective and judicious application. Trial registration PROSPERO registration number: CRD42024569842.